Macrocycle-size-modulated Cl− microenvironments in cationic mesoporous polymers for rapid capture of volatile iodine - Zhangjie Huang; Jinkai Qiu; Liang Liu; Qimeng Sun; Xiaoyong Xia; Cheng Lian; Dongyun Chen; Hua Li; Qingfeng Xu; Jianmei Lu (Chemical Engineering Journal, 2026)

A star’s death by a thousand cuts: the runaway periodic eruptions of AT2023uqm - Yibo Wang; Tinggui Wang; Shifeng Huang; Jiazheng Zhu; Ning Jiang; Wenbin Lu; Rongfeng Shen; Shiyan Zhong; Dong Lai; Yi Yang; Xinwen Shu; Tianyu Xia; et al. (Science Bulletin, 2026)

Ecosystem collapses in Southwest China revealed by stalagmite records during the Mid-to-Late Holocene - Shaohua Yang; Chuntong He; Shitao Chen; Qingfeng Shao; Ye Zhu; Lei Lu; Hongwei Yin; Yijia Liang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Chlorine enrichment mechanisms in coals from the middle Jurassic of Northwestern China: Evidence from Cryo-SEM and geochemical analyses - Xinyi Xu; Wenfeng Wang; Qingfeng Lu; Wenlong Wang; Bofei Zhang (International Journal of Coal Geology, 2026)

Fish-gill-inspired hierarchical membranes with charge-repulsion-mediated ion-selective nanostructures for enhanced desalination performance - Yingxue Zhang; Wei Sun; Haoyu Jiang; Qiuxuan Zhou; Najun Li; Qingfeng Xu; Hua Li; Dongyun Chen; Jianmei Lu (Chemical Engineering Journal, 2026)

Enhanced removal of organic pollutants and effective suppression of chlorinated/brominated by-products in heat/peroxymonosulfate system by adding sodium percarbonate - Yao Huang; Chenyu Tang; Bingyu Lu; Jianhang Li; Lukai Zhuang; Minfeng Wang; Haoqiang Tan; Qingfeng Cheng; Qingsong Li; Bo Sun; Jing Zou (Journal of Environmental Chemical Engineering, 2026)

Improvement of probiotic tolerance to hyperosmotic environments by whey protein-citrus pectin conjugate: effect on the physicochemical, structural, survival of probiotic microencapsulation - Xuan Lu; Ning Zhang; Jingru Chen; Xinyi Li; Suo Zheng; Fei Liu; Qingfeng Ban; Xiangchen Meng (Food Research International, 2026)

SuFEx-enabled functional materials in environmental treatment, energy and data storage, biomedicine and organic synthesis and catalysis - Haibo Wan; Xinyi Deng; Daoyong Chen; Peng Wu; Qingfeng Xu; Jianmei Lu (Chemical Engineering Journal, 2026)

A novel biogas liquefaction process adopting dual nitrogen expansion cycle with carbon dioxide pre-cooling - Yanjun Huang; Qingfeng Jiang; Xiaofei Lu; Xiao Song; Jiangchao Wang; Huaibin Li (International Journal of Refrigeration, 2026)

Regular and mechanism of millennial scale weak monsoon events during the late MIS7 to early MIS6.5 period - Shaohua Yang; Shitao Chen; Yongjin Wang; Bin Zhao; Yijia Liang; Zhenjun Wang; Zhenqiu Zhang; Quan Wang; Qingfeng Shao; Lei Lu; Chuan-Chou Shen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Enrichment mechanism and clean utilization of sodium-iron in high alkali and high iron coal in Beishan coal Mine, Xinjiang - Jiaxin Li; Hongyang Bai; Wenfeng Wang; Hengyan Liu; Kexin Che; Peng Wang; Qingfeng Lu (Fuel, 2026)

Gaussian Function Affine Transformation Model: A Bridge Between Laboratory and Downhole Logging NMR in Shale Oil Reservoirs - Junjie Wang; Pengfei Zhang; Weizheng Gao; Wenbiao Li; Nengwu Zhou; Guohui Chen; Qingfeng Li; Chao Liu; Shuangfang Lu (Natural Resources Research, 2026)

Stabilization mechanisms, cell density, and survival of probiotic encapsulation prepared with thiolated hyaluronic acid-whey protein complex: For potential colon targeting probiotic delivery system - Ning Zhang; Xuan Lu; Jingru Chen; Xinyi Li; Suo Zheng; Fei Liu; Qingfeng Ban; Xiangchen Meng (Food Research International, 2026)

Mechanisms of growth enhancement in Tartary buckwheat by endophytic fungi: a transcriptomic and metabolomic insight - Qiqi Xie; Yujie Jia; Jiwen Tao; Tongliang Bu; Xinyu Zhang; Yirong Xiao; Qingfeng Li; Zizhong Tang; Lu Zhang; Gonghong Li; Junhua Liao (Plant and Soil, 2026)

Facilitating redox cycles of copper species by peroxydisulfate in the copper-catalyzed Fenton-like system for enhanced oxidation of organic contaminants - Bingyu Lu; Jianying Wu; Chenyu Tang; Jing Zou; Bo Sun; Minfeng Wang; Qingfeng Cheng; Haoqiang Tan; Qingsong Li; Jun Ma (Water Research, 2026)

Macrocyclic Schiff-base covalent organic polymers with synergistic multi-sites for high-temperature iodine/methyl iodide capture - Liang Liu; Zhonglin Ma; Jiaqing Huang; Zhangjie Huang; Jiajia Li; Jinkai Qiu; Ying Zheng; Cheng Lian; Dongyun Chen; Long Chen; Qingfeng Xu; Jianmei Lu (Journal of Hazardous Materials, 2026)

Seismic behaviour of H-shaped steel-concrete-steel composite walls with innovative C-channel connectors to enhance resilience - Jin Wang; Yan Lu; Qingfeng Liu (Engineering Structures, 2026)

SuFEx-derived macrocyclic polysulfates for efficient dual capture of methyl iodide and iodine - Shuai Shi; Zhonglin Ma; Long Chen; Yuqi Zhang; Haibin Shi; Qingfeng Xu; Jianmei Lu (Chemical Engineering Journal, 2025)

Centennial- to multidecadal-scale monsoon precipitation variability during the mid-Holocene - Yifei Wang; Zhenqiu Zhang; Yongjin Wang; Kan Zhao; Yijia Liang; Kui Gao; Jianshun Chen; Qingfeng Shao; Zeji Lu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Triple-synergistic dual-macrocyclic polysulfates for efficient capture of diverse iodine species - Jiajia Li; Jiaqing Huang; Xiaoyong Xia; Liang Liu; Chunyue Xu; Jinkai Qiu; Cheng Lian; Qingfeng Xu; Jianmei Lu (Journal of Environmental Chemical Engineering, 2025)

Editorial Expression of Concern: HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

A triazine-tri-imidazole based cationic covalent organic polymer featuring high recyclability and radiation tolerance for efficient Re(Tc)O4- sequestration - Jiaqing Huang; Xiaoyong Xia; Jiajia Li; Liang Liu; Chunyue Xu; Jinkai Qiu; Cheng Lian; Qingfeng Xu; Jianmei Lu (Journal of Hazardous Materials, 2025)

Mineralogy and elemental geochemistry of Pennsylvanian high-sulfur coals in the Huanghebei Coalfield, Shandong, Northern China: Implications for the enrichment and controlling factors of U - Bofei Zhang; Wenfeng Wang; Qingfeng Lu; Wenlong Wang; Xiaozhen Teng; Long Chen (International Journal of Coal Geology, 2025)

Thiazolyl-conjugated porous polymer-coated CdZnS for synergistic adsorption and photocatalytic degradation of bisphenol A and with enhanced H2O2 production - Wanjun Xu; Yingxue Zhang; Shihong Dong; A.S. Gubin; I.N. Pugacheva; Najun Li; Qingfeng Xu; Hua Li; Dongyun Chen; Jianmei Lu (Chemical Engineering Journal, 2025)

Deciphering the regulatory network of carbon isotope discrimination in bread wheat through genome-wide association studies and genomic prediction - Qingfeng Dong; Shan Lu; Hao Ren; Dezheng Liu; Shen-ao Gao; Xuefen Cai; Shanshan Zhang; Muhammad Ateeq; Liang Chen; Yin-gang Hu (Theoretical and Applied Genetics, 2025)

Physiological and transcriptomic responses of fall armyworm, Spodoptera frugiperda to host-plant switching - Jun Peng; Renwen Zheng; Jinyuan Zhao; Jinhui Zhang; Qianqian Li; Dongyan Huang; Xin Zhou; Lijuan Liu; Zhuocong Li; Xiaoman Ning; Sihan Lu; Qingfeng Tang (Journal of Pest Science, 2025)

Multi-objective optimization of the plate-fin heat exchanger coupled with ortho-para hydrogen conversion for hydrogen liquefaction - Xiangkun Tao; Qingfeng Jiang; Xiaofei Lu; Xiao Song; Jiangchao Wang; Hansheng Feng (International Journal of Refrigeration, 2025)

Novel QTLs/genes affecting single stem elasticity, stem strength, and three lodging indices in bread wheat (Triticum aestivum L.) identified by genome-wide association analysis - Hao Ren; Shan Lu; Siting Li; Qingfeng Dong; Dezheng Liu; Roi Ben-David; Liang Chen; Yin-Gang Hu (Theoretical and Applied Genetics, 2025)

Gut bacteria of the fall armyworm, Spodoptera frugiperda, promote host resistance against the toxic effects of lufenuron - Qianqian Li; Renwen Zheng; Jinyuan Zhao; Sihan Lu; Yue Liu; Dongyan Huang; Jinhui Zhang; Lijuan Liu; Xin Zhou; Qingfeng Tang (Journal of Pest Science, 2025)

Toluene-induced framework expansion in carbazole-based porous organic polymers anchored with Cu-ZnIn2S4 for ultrafast azeotropic wastewater recovery - Yingxue Zhang; Xunxun Li; Wanjun Xu; Yuxin Cheng; Shihong Dong; Najun Li; Qingfeng Xu; Hua Li; Dongyun Chen; Jianmei Lu (Chemical Engineering Journal, 2025)

Deciphering the regulatory network of lignocellulose biosynthesis in bread wheat through genome-wide association studies - Qingfeng Dong; Hao Ren; Xuefen Cai; Yujie Zhang; Shan Lu; Dezheng Liu; Muhammad Ateeq; Liang Chen; Yin-Gang Hu (Theoretical and Applied Genetics, 2025)

Hydroclimate variability over East Asia linked to ocean circulation, Antarctic and Pacific temperature changes during the LGM - Haixin Lu; Fucai Duan; Zhenqiu Zhang; Jianshun Chen; Junji Zhu; Qingfeng Shao; Yongjin Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Effect of different Agrobacterium rhizogenes strains on hairy root induction and analysis of metabolites in Physalis peruviana L. - Yijia Zhong; Zhie Zhou; Zhongping Yin; Lu Zhang; Qingfeng Zhang; Yihai Xie; Jiguang Chen (Journal of Plant Physiology, 2025)

Efficient As(III) removal from acidic wastewater by polymorphism control of FeS - Jing Chen; Qingfeng Dong; Jing Li; Chaobo Zhang; Guang Fu; Zhanqing Lu (Journal of Water Process Engineering, 2025)

Mining genomic regions associated with stomatal traits and their candidate genes in bread wheat through genome-wide association study (GWAS) - Dezheng Liu; Shan Lu; Renmei Tian; Xubin Zhang; Qingfeng Dong; Hao Ren; Liang Chen; Yin-Gang Hu (Theoretical and Applied Genetics, 2025)

Recognition of dispersed organic matter macerals using YOLOv5m model with convolutional block attention module - Yuanzhe Wu; Qingfeng Lu; Wenfeng Wang; Wenlong Wang; Jiaxin Li; Xinyi Xu; Kexin Che (Fuel, 2024)

Characterization of shale oil and water micro-occurrence based on a novel method for fluid identification by NMR T2 spectrum - Junjie Wang; Shuangfang Lu; Pengfei Zhang; Qingfeng Li; Yajie Yin; Wenbiao Li; Nengwu Zhou; Guohui Chen; Yangjian Yi; Chenxi Wu (Fuel, 2024)

Engineering SuFEx-derived macrocyclic polysulfates for superior dynamic iodine capture at high temperatures - Shuai Shi; Zhonglin Ma; Haibo Wan; Long Chen; Qingfeng Xu; Jianmei Lu (Chemical Engineering Journal, 2024)

Distribution and transformation of potentially toxic elements in cracks under coal mining disturbance in farmland - Yin Lu; Xin Xiao; Yan Liang; Junchi Li; Chunying Guo; Lili Xu; Qingfeng Liu; Yu Xiao; Shiyuan Zhou (Environmental Geochemistry and Health, 2024)

Global daily mask use estimation in the pandemic and its post environmental health risks: Analysis based on a validated dynamic mathematical model - Ying Zhang; Fei Jiang; Fengmin Li; Shaoyong Lu; Zihao Liu; Yuwen Wang; Yiming Chi; Chenchen Jiang; Ling Zhang; Qingfeng Chen; Zhipeng He; Xiaoli Zhao; et al. (Journal of Hazardous Materials, 2024)

U-series in situ dating of secondary carbonates associated with rock paintings using LA-MC-ICPMS - Yanuo Jiao; Yue Liu; Zeji Lu; Rainer Grün; Qingfeng Shao (Quaternary Geochronology, 2024)

Grafting small organic molecules on donor-acceptor polymers to regulate electron push-pull interactions for efficient H2O2 production - Shuang Zhao; Najun Li; Qingfeng Xu; Hua Li; Jianmei Lu; Dongyun Chen (Chemical Engineering Journal, 2024)

A quaternary ammonium cyclodextrin polymer for efficient photocatalytic production of hydrogen peroxide from pure water - Bingshu Jiang; Dongyun Chen; Najun Li; Qingfeng Xu; Hua Li; Jianmei Lu (Chemical Engineering Journal, 2024)

Metagenomic insights into the diversity of 2,4-dichlorophenol degraders and the cooperation patterns in a bacterial consortium - Shunli Hu; Chuangchuang Xu; Yanghe Xie; Lu Ma; Qingfeng Niu; Guomin Han; Junwei Huang (Science of The Total Environment, 2024)

Environmental-friendly enzyme nanoreactors with high adsorption capacity for long-time and efficient treatment of pollutants under visible light irradiation - Shuting Huang; Dongyun Chen; Najun Li; Qingfeng Xu; Hua Li; Jianmei Lu (Chemical Engineering Journal, 2024)

Prediction Model of the Sound Speed of Seafloor Sediments on the Continental Shelf of the East China Sea Based on Empirical Equations - Guangming Kan; Junjie Lu; Xiangmei Meng; Jingqiang Wang; Linqing Zhang; Guanbao Li; Baohua Liu; Qingfeng Hua; Mujun Chen (Journal of Marine Science and Engineering, 2023)
Based on the data of the acoustic and physical properties of seafloor sediments obtained on the continental shelf area of the East China Sea (ECS), prediction equations of the sediment sound speed based on single and dual parameters were established, and the correlation of the sound speed with physical parameters was discussed. The results show that the sediment sound speed (c) is strongly correlated with water content (w), density (ρ), void ratio (e), mean grain size (Mz) and median grain size (Md), and the coefficient of determination R2 of the empirical regression equation is generally greater than 0.80, while the empirical regression equation coefficient of determination R2 of the compression coefficient (a) and compression modulus (E) are slightly lower, with 0.79 and 0.73, respectively. The coefficients of determination of the dual parameter regression equations between sediment sound speed with physical property parameters are generally higher than those of the single parameter equations, which are all higher than 0.90 indicating better prediction performance. The sensitivity of the physical parameters to the sound speed was analyzed, and the result shows that the sequence of sensitivity from high to low influence on sediment sound speed is void ratio, density, compressibility coefficient, median grain size and mean grain size. The prediction equations established in this study are a good extension and supplement to marine geoacoustic models and is of great significance for obtaining the acoustic properties of the seafloor sediments on the shelf of the East China Sea.

Diversification of faunal exploitation strategy and human-climate interaction in Southern China and Southeast Asia during the last deglaciation - Yongxiu Lu; Feng Gao; Yiren Wang; Minmin Ma; Aifeng Zhou; Ruiliang Liu; Hiroki Kikuchi; Lele Ren; Qingfeng Shao; Lin Chen; Yongxiang Xu; Haoran Li; et al. (Quaternary Science Reviews, 2023)

Graphene aerogel-doped CoFe2O4/MoS2 sheets for magnetic oil absorption and the degradation of contaminants - Xin Xiang; Wenxuan Deng; Zhiyi He; Dongyun Chen; Najun Li; Qingfeng Xu; Hua Li; Jianmei Lu (Journal of Environmental Chemical Engineering, 2023)

Correction to: Clinical Significance and Influencing Factors of Microvascular Tissue Reperfusion After Macrovascular Recanalization - Xuesong Bai; Fan Yu; Qiuyue Tian; Wei Li; Arman Sha; Wenbo Cao; Yao Feng; Bin Yang; Yanfei Chen; Peng Gao; Yabing Wang; Jian Chen; et al. (Translational Stroke Research, 2023)

Enhanced VOCs adsorption and oxidation by hydrophobic-layer-modified YMn2O5 mullite catalyst with ultralow single-atom Pt loading - Jiaqin He; Yaru Wang; Xunxun Li; Jun Xiao; Yunchong Liu; Hua Li; Najun Li; Qingfeng Xu; Dongyun Chen; Jianmei Lu (Chemical Engineering Journal, 2023)

Distribution and transformation of potentially toxic elements in crack under coal mining disturbance - Junchi Li; Qinxue Yu; Ruoxi Qian; Xin Xiao; Yan Liang; Ping Luo; Hui Wang; Yin Lu; Lili Xu; Qingfeng Liu; Yu Xiao (Environmental Monitoring and Assessment, 2023)

The impact of ambient air pollutants on childhood respiratory system disease and the resulting disease burden: a time-series study - Wenbin Shen; Xue Li; Qingfeng Fang; Guoao Li; Wei Xiao; Yueyang Wu; Jianjun Liu; Wenlei Hu; Huanhuan Lu; Fen Huang (International Archives of Occupational and Environmental Health, 2023)

Insecticidal potential of a Consolida ajacis extract and its major compound (ethyl linoleate) against the diamondback moth, Plutella xylostella - Jun Peng; Zihan Chen; Xueqian Chen; Renwen Zheng; Sihan Lu; Muhammad Seyab; Fan Yang; Qianqian Li; Qingfeng Tang (Pesticide Biochemistry and Physiology, 2023)

Boosted photogenerated charge carrier separation by synergy of oxygen and phosphorus co-doping of graphitic carbon nitride for efficient 2-chlorophenol photocatalytic degradation - Zhuzhu Zhang; Qimeng Sun; Rui Ji; Dongyun Chen; Najun Li; Hua Li; Qingfeng Xu; Huilong Dong; Jianmei Lu (Chemical Engineering Journal, 2023)

Biomimetic porphyrin-modified 3D porous composite material adsorption enhances photocatalytic CO2 reduction and tetracycline oxidative degradation - Mengmeng Wang; Yingxue Zhang; Dongyun Chen; Najun Li; Qingfeng Xu; Hua Li; Jianmei Lu (Chemical Engineering Journal, 2023)

Clinical Significance and Influencing Factors of Microvascular Tissue Reperfusion After Macrovascular Recanalization - Xuesong Bai; Fan Yu; Qiuyue Tian; Wei Li; Araman Sha; Wenbo Cao; Yao Feng; Bin Yang; Yanfei Chen; Peng Gao; Yabing Wang; Jian Chen; et al. (Translational Stroke Research, 2023)

Methamphetamine induces cardiomyopathy through GATA4/NF-κB/SASP axis-mediated cellular senescence - Xu Zhao; Jiancong Lu; Cui Zhang; Chuanxiang Chen; Manting Zhang; Jingyi Zhang; Qingfeng Du; Huijun Wang (Toxicology and Applied Pharmacology, 2023)

Experimental Study on the Influence of Temperature on Rock Salt Creep - Zhikai Dong; Yinping Li; Haoran Li; Ziheng Wang; Xilin Shi; Xiangsheng Chen; Qingfeng Lu (Rock Mechanics and Rock Engineering, 2023)

Identification of DNA methylation and genetic alteration simultaneously from a single blood biopsy - Xiaomin Chen; Jiahui Liu; Jun Li; Yinpeng Xie; Zichen Yu; Lu Shen; Qingfeng Liu; Wei Wu; Qiang Zhao; Haoxiang Lin; Gaotong Liu; Qiuping Luo; et al. (Genes & Genomics, 2023)

Enhanced remediation of phenanthrene in water and soil by novel biochar-immobilized bacterial microspheres - Kai Wang; Yang Sun; Dongyun Chen; Qingfeng Xu; Najun Li; Hua Li; Jianmei Lu (Chemical Engineering Journal, 2023)

Association of biomass fuel use with the risk of vision impairment among Chinese older adults: a cohort study - Ying Zhou; Minzhi Xu; Pan Ke; Hongkun Di; Yong Gan; Jing Feng; Xin Meng; Cheng Su; Qingfeng Tian; Zuxun Lu (Environmental Science and Pollution Research, 2023)

Geochemistry of rare earth elements and yttrium in Late Permian coals from the Zhongliangshan coalfield, southwestern China - Qingfeng Lu; Shenjun Qin; Hongyang Bai; Wenfeng Wang; De’e Qi; Xin He; Bofei Zhang (Frontiers of Earth Science, 2023)

Ni-Mn spinel aerogel catalysts with adsorption induced superior activity for Low-Temperature toluene oxidation - Jiaqin He; Xunxun Li; Yaru Wang; Jun Xiao; Yunchong Liu; Hua Li; Najun Li; Qingfeng Xu; Jinghui He; Dongyun Chen; Jianmei Lu (Chemical Engineering Journal, 2023)

Z- scheme heterojunction of BiOI nanosheets grown in situ on NH2-UiO-66 crystals with rapid degradation of BPA in real water - Rui Ji; Zhuzhu Zhang; Lechen Tian; Liujun Jin; Qingfeng Xu; Jianmei Lu (Chemical Engineering Journal, 2023)

Geochemistry of Late Permian coals from the Moxinpo mine, Chongqing, Southwestern China: Emphasis on petrology, minerals, and organic matter - Qingfeng Lu; Shenjun Qin; Wenfeng Wang; Kang Gao; Jingkai Xing (Applied Geochemistry, 2023)

Geochemistry of Late Permian coals from the Yueliangtian coal deposit, Guizhou: Evidence of sediment source and evaluation on critical elements - Qingfeng Lu; Shenjun Qin; Wenfeng Wang; Qian Wang; Shuai Kang (Science of The Total Environment, 2023)

Low quantity of Pt loaded onto CeCoOx nanoboxes: Surface–rich reactive oxygen species for catalytic oxidation of toluene - Yunchong Liu; Xunxun Li; Dongyun Chen; Najun Li; Qingfeng Xu; Hua Li; Jinghui He; Jianmei Lu (Journal of Hazardous Materials, 2023)

Sulfonate-modified calixarene-based porous organic polymers for electrostatic enhancement and efficient rapid removal of cationic dyes in water - Lechen Tian; Shiyuan Zhou; Jiaojiao Zhao; Qingfeng Xu; Najun Li; Dongyun Chen; Hua Li; Jinghui He; Jianmei Lu (Journal of Hazardous Materials, 2023)

Lead-Free Cs3Bi2Br9 perovskite In-situ growth on 3D Flower-like g-C3N4 microspheres to improve photocatalytic performance - Bingke Xie; Dongyun Chen; Najun Li; Qingfeng Xu; Hua Li; Jianmei Lu (Chemical Engineering Journal, 2023)

Shallow groundwater enhances water productivity of maize in arid area - Jialu Dai; Ruiping Li; Qingfeng Miao; Congcong Li; Yaoze Lu; Zhimin Hua (Irrigation Science, 2022)

Fifty years of Quaternary palynology in the Tibetan Plateau - Lingyu Tang; Caiming Shen; Houyuan Lu; Chuanhai Li; Qingfeng Ma (Science China Earth Sciences, 2021)

Alpha 1-antichymotrypsin may be a biomarker for the progression of amnestic mild cognitive impairment - Shunjie Liu; Junhao Pan; Ke Tang; Qingfeng Lei; Lu He; Xiaodong Cai; Zhong Li (Acta Neurologica Belgica, 2021)

Characterization, identification and evaluation of a novel wheat-Agropyron cristatum (L.) Gaertn. disomic addition line II-30-5 - Qingfeng Li; Yuqing Lu; Cuili Pan; Zhangjun Wang; Fenglou Liu; Jinpeng Zhang; Xinming Yang; Xiuquan Li; Weihua Liu; Lihui Li (Genetic Resources and Crop Evolution, 2020)

Lake water-level fluctuation forecasting using machine learning models: a systematic review - Senlin Zhu; Hongfang Lu; Mariusz Ptak; Jiangyu Dai; Qingfeng Ji (Environmental Science and Pollution Research, 2020)

Erratum to: Molecular characteristics of the ompA gene of serotype B Chlamydia trachomatis in Qinghai Tibetan primary school students - Xue Li; Shaoya Zhang; Qingfeng Liang; Mei Wang; Ailian Hu; Xiuyuan Li; Benshan Yang; Mingxin Zhang; Ningli Wang; Xinxin Lu (Science China Life Sciences, 2016)

Study of infectious conjunctivitis among children in rural areas of Qinghai province - Qingfeng Liang; Xinxin Lu; Mei Wang; Lei Tian; Antoine Labbé; Ailian Hu (Science China Life Sciences, 2016)

Molecular characteristics of the ompA gene of serotype B Chlamydia trachomatis in Qinghai Tibetan primary school students - Xue Li; Shaoya Zhang; Qingfeng Liang; Mei Wang; Ailian Hu; Xiuyuan Li; Benshan Yang; Mingxin Zhang; Ningli Wang; Xinxin Lu (Science China Life Sciences, 2016)

The Report of Sustained Low-Efficiency Dialysis (SLED) Treatment in Fifteen Patients of Severe Snakebite - Junzhang Cheng; Dan Wang; Shouliang Hu; Hong Jiang; Hongzhu Lu; Qingfeng Lei; Juncheng Liu; Fanli Yuan; Rong Chen (Cell Biochemistry and Biophysics, 2014)

Comparison of the Therapeutic Effectiveness of Sustained Low-Efficiency Dialysis (SLED) with Continuous Blood Purification (CBP) in Critically Ill Patients - Junzhang Cheng; Shouliang Hu; Hongzhu Lu; Qingfeng Lei; Juncheng Liu; Fanli Yuan; Rong Chen (Cell Biochemistry and Biophysics, 2013)

Diversity of Gene Cassette Promoter Variants of Class 1 Integrons in Uropathogenic Escherichia coli - Quhao Wei; Xiaofei Jiang; Min Li; Gang Li; Qingfeng Hu; Huoxiang Lu; Guoqiang Chen; Yonglie Zhou; Yuan Lu (Current Microbiology, 2013)

HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Overexpressed mutant optineurin(E50K) induces retinal ganglion cells apoptosis via the mitochondrial pathway - Qingfeng Meng; Jia Lv; Hongyan Ge; Lu Zhang; Fei Xue; Yuanmao Zhu; Ping Liu (Molecular Biology Reports, 2012)

Acute effects of warm footbath on arterial stiffness in healthy young and older women - Qingfeng Hu; Weili Zhu; Yili Zhu; Lu Zheng; Richard L. Hughson (European Journal of Applied Physiology, 2012)

Nose-to-Brain Transport Pathways of Wheat Germ Agglutinin Conjugated PEG-PLA Nanoparticles - Qingfeng Liu; Yehong Shen; Jie Chen; Xiaoling Gao; Chengcheng Feng; Lu Wang; Qizhi Zhang; Xinguo Jiang (Pharmaceutical Research, 2012)